Rigidity Measures. On Constitutional Amendment - Anckar, Dag (Advances in Social Sciences Research Journal, 2017)
Findings in the literature on the explanatory power of constitutional rigidity tend to be inconsistent and at times even contradictory. One possible explanation for this state of affairs is that methods for operationalizing and measuring rigidity levels are still somewhat intuitive and un-precise. Classifying and categorizing constitutional amendment procedures and strictly applying a view of rigidity as a constitutional variable, an attempt is made here to design a rigidity grading that runs from a zero point on a scale that makes use of half-point as well as full-point intervals. Observations on methods for assessing patterns of legislative and popular sovereignty as well as combinations of these sovereignty types are followed by observations on varieties of double decision rules. Illustrations of the multitude of amendment politics are inserted frequently in the presentation, as are extracts from relevant sections of constitutional law in different countries.